CONTEMPORARY DIFFICULTIES IN INDIAN POLITICS - Honnanjanaiah D R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today, Indian politics is engulfed by a multidimensional crisis that is probing its democratic resilience. At the core of these challenges is growing political polarization propelled by increasing majoritarian nationalism and ideological extremism that fuels communal divisions and stifles pluralist voices. The centralising impulses have stretched federalism, as with many controversial policies such as the farm laws that were eventually repealed and tussles over the distribution of Goods and Service tax revenues, leading state governments to retaliate against the imposition of national economic policies and initiate conversations on fiscal federalism. Once again, economic growth has not translated into the disappearance of lopsided socioeconomic inequality with unemployment, agrarian distress, and informal sector vulnerability leading to unprecedented levels of agitation and disenchantment towards governance. Institutions essential to democracy — the courts, media and investigative agencies — find their credibility in free fall when they are accused of executive interference and depriving themselves of independence, undercutting accountability. There is no social justice, as caste discrimination, gender violence and minority marginalisation catalyse identity-based mobilisations. All of which democratically defines electoral integrity: populist rhetoric, opaque campaign financing and the alleged weaponization of state agencies. Meanwhile, environmental destruction and geopolitical tensions distract from sustainable development. These challenges call for structural reforms, collaborative federalism, responsible policymaking and offer opportunities to nurture the roots of democracy. Without bipartisan dialogue and inclusive reforms, however, India will simply risk entrenching governance deficits and social fragmentation and compromising its constitutional ideals of justice, liberty and equality. In an increasingly polarized polity, urgent structural and civic interventions are essential to support the nexus of governance and democracy.